Evolution through intellectual property rights in the aquaculture sector: reshaping aquaculture production networks - Alsaleh, Mohd; Abdul-Rahim, A.S.; Qi, Long; Yuan, Yuan (Springer Science and Business Media, 2024)
In aquaculture, the intellectual property issues are the risks to the stability of copyright, trademark, patent, and other domains of intellectual property rights. As a basis of the intellectual property of marine law in the European Union region (EU27), the interests and needs of creators and the public are in balance. When such a balance is not upheld, then there is a compromise of the protection of intellectual property rights. Thus, the novelty can be formulated as follows: The analysis of the impact of the intellectual property factors on the aquaculture industry growth in the EU13 and EU14 during the 1990–2023 period. The main findings were estimated using ordinary least squares (OLS), two-stage least squares (2SLS) and robust least square (RLS) to overcome the endogeneity problem. The degree of the impact reveals that the protection of IPRs and ICRs, that is, intellectual property rights and intellectual capital rights, significantly influence the growth of the aquaculture industry in the EU14 developed countries rather than in the EU13 developing countries. However, the actual values of the three estimators reveal that economic growth, market size, and governance significantly affect the aquaculture industry growth in EU13 developing countries than in EU14 developed countries. Therefore, according to the conclusions of this research, the policies that should be prioritized by the policymakers in EU13 developing countries are those that focus on the improvement of the development of intellectual property rights and intellectual capital rights plays. As it is suggested in this research, it is recommended that policymakers in EU14 developed countries enhance the blue governance, marine market size, and the development of aquatic economy and blue farming.